2017
DOI: 10.1101/223032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A genome-wide association study for host resistance to Ostreid Herpesvirus in Pacific oysters (Crassostrea gigas)

Abstract: 42Ostreid herpesvirus (OsHV) can cause mass mortality events in Pacific oyster indicating a significant but low heritability for the binary trait of survival and also for 60 viral load measures (h2 0.12 -0.25). A genome-wide association study highlighted a 61 region of linkage group 6 containing a significant QTL affecting host resistance. 62These results are an important step towards identification of genes underlying 63 resistance to OsHV in oyster, and a step towards applying genomic data to enhance 64 sel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 41 publications
7
45
0
Order By: Relevance
“…The approximately 20 000 mapped SNPs correspond to 1880 scaffolds and 133 contigs, according to the latest oyster genome assembly (GCA_000297895.1; Zhang et al ). We observed that approximately 38% (719 out 1880) of the scaffolds with informative markers showed evidence of errors in the assembly, owing to assignment to at least two distinct LGs in our map, following a similar pattern to that described in our previous linkage map (Hedgecock et al ; Gutierrez et al ).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The approximately 20 000 mapped SNPs correspond to 1880 scaffolds and 133 contigs, according to the latest oyster genome assembly (GCA_000297895.1; Zhang et al ). We observed that approximately 38% (719 out 1880) of the scaffolds with informative markers showed evidence of errors in the assembly, owing to assignment to at least two distinct LGs in our map, following a similar pattern to that described in our previous linkage map (Hedgecock et al ; Gutierrez et al ).…”
Section: Resultssupporting
confidence: 83%
“…The linkage map construction resulted in approximately 20 000 SNPs distributed across 10 linkage groups in similar positions to those previously described in a different population (Gutierrez et al ). As with previous linkage maps, the mapping of SNPs located within single reference genome contigs to multiple linkage groups highlighted putative reference genome assembly errors (Zhang et al ; Hedgecock et al ).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations